2006
DOI: 10.1002/ffj.1681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative examination of the essential oils of Anthemis ruthenica and A. arvensis wild‐growing in Serbia

Abstract: The essential oils from the aerial parts of Anthemis ruthenica and Anthemis arvensis, wild-growing in Serbia, obtained by hydrodistillation were analyzed using GC and GC/MS. A total of 75 and 81 components were identified in A. ruthenica and A. arvensis, respectively. The major constituents of A. ruthenica oil were β β β β β-pinene (3.6%), 1,8-cineol (6.8%), 4-terpineol (6.2%), α α α α α-terpineol (3.6%), isophyllocladene (5.4%) and palmitic acid (9.9%). The oil of A. arvensis showed a high content of non-terp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…The main constituents in both oils were germacrene D (8.3 -11.3%) and terpinen-4-ol (6.3 -7.3%), whereas oil from Kovin population additionaly contained b-pinene (7.5%) and borneol (5.7%), and the oil from Stara Palanka epi-a-cadinol (5.5%) in prominent amounts. Previous investigation of the oil of A. ruthenica, originated also from Serbia, but from different location [16], revealed that major compounds were palmitic acid (9.9%), 1,8-cineole (6.8%), 4-terpineol (6.2%), and isophyllocladene (5.4%), while in our samples palmitic acid and isophyllocladene were not detected.…”
contrasting
confidence: 78%
“…The main constituents in both oils were germacrene D (8.3 -11.3%) and terpinen-4-ol (6.3 -7.3%), whereas oil from Kovin population additionaly contained b-pinene (7.5%) and borneol (5.7%), and the oil from Stara Palanka epi-a-cadinol (5.5%) in prominent amounts. Previous investigation of the oil of A. ruthenica, originated also from Serbia, but from different location [16], revealed that major compounds were palmitic acid (9.9%), 1,8-cineole (6.8%), 4-terpineol (6.2%), and isophyllocladene (5.4%), while in our samples palmitic acid and isophyllocladene were not detected.…”
contrasting
confidence: 78%
“…AMDIS software was used to calculate Kovats retention indices. Further identification was made by comparing their mass spectra with these stored in NIST 08 and with mass spectra from the literature [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The relative concentrations of the components were obtained by peak areas normalization without applying correction factors.…”
Section: Methodsmentioning
confidence: 99%
“…The seeds of peanuts (A. hypogaea) contained the highest amounts of oleic (C18:1) and linoleic (C18:2) acids reaching 50% and 30%, respectively [30]. In the essential oil from the aerial parts of A. arvensis, the palmitic acid achieved~21% [42], whereas 8.8% in the seeds with the total PUFA/SFA ratio equal 7.17 [34]. In the seeds of C. populnea, the most abundant among fatty acids were palmitic (C16:0)-40%, oleic (C18:1n-9)-27%, stearic (C18:0)-16.5%, and linoleic (C18:2n-6)-11.86% acids.…”
Section: Fatty Acids Composition In Plantsmentioning
confidence: 99%